Transnational ties with the ethnic homeland: the case of Korean women of the CIS in marital migration (Journal of Oriental Studies, 2020)
Every year, tens of thousands of women from developing countries cross borders to marry men from developed countries. Men in Western Europe and the United States are looking for future partners from Russia and Eastern Europe, while men in East Asia and Australia find wives in the countries of Southeast Asia. Transnational marriage puts these women in a vulnerable position because women lack the resources, language skills, social support and legal protection in receiving countries. For more than twenty years of socio-economic, scientific, educational, cultural cooperation with the countries of the former Soviet Union, South Korea has become a recognizable and attractive brand for everyone. One of the results is an increase in transnational marriages, most often ethnic women of the CIS. The author considers the features of the international marriage of ethnic Koreans married in South Korea. A “Eurocentric” perspective on the choice of a South Korean citizen as a marriage partner for CIS girls can greatly assist Korean government and non-governmental organizations in adjusting policies to attract migrant women, as well as in implementing policies for the integration and adaptation of Russianspeaking ethnic Korean women in Korea. Key words: Interethnic marriage, CIS, historical homeland, marital migration, Koreans of the CIS.